Development and characterization of a halo-thermophilic bacterial consortium for decolorization of azo dye. (June 2021) - Guo, Guang; Liu, Chong; Hao, Jiuxiao; Tian, Fang; Ding, Keqiang; Zhang, Can; Yang, Feng; Liu, Tingfeng; Xu, Jin; Guan, Zhengbing
Abstract: Textile wastewater is characterized by high salinity and high temperature, and azo dye decolorization by mixed cultures under extreme salinity and thermophilic environments has received little attention. High salinity and temperature inhibit the biodecolorization efficiency in textile wastewater. In the present study, a halo-thermophilic bacterial consortium (HT1) that can decolorize azo dye at 10% salinity and 50 °C was enriched. Bacillus was the dominant genus, and this genus may play a key role in the decolorization process. HT1 can decolorize metanil yellow G (MYG) at a wide range of pH values (6–8), temperatures (40–60 °C), dye concentrations (100–200 mg/L) and salinities (1–15%). Laccase, manganese peroxidase, lignin peroxidase and azoreductase are involved in the decolorization process of MYG. In addition, the decolorization pathway of MYG was proposed based on GC-MS and FTIR results. The toxicity of MYG decreased after decolorization by HT1. A metagenomic sequencing approach was applied to identify the functional genes involved in degradation. Overall, this halo-thermophilic bacterial consortium could be a promising candidate for the treatment of textile wastewater under elevated temperature and salinity conditions.